Corrupt reciprocity: An experiment - Johann Graf Lambsdorff; Björn Frank (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2007)
We let students play a corruption game, embedded into a variant of the ultimatum game. Those allotted the role of public servants chose between whistleblowing, opportunism and reciprocity by delivery (of a contract) and those acting as businesspeople chose how to frame the game and whether to blow the whistle. While opportunism and abstaining from whistleblowing is the Nash equilibrium, another likely outcome was that businesspeople allocate resources to punishing public servants for non-delivery, exhibiting a preference for negative reciprocity. Anticipating this, public servants might tend to reciprocate or blow the whistle upfront. Female public servants were more inclined to behave opportunistically; female businesspeople were less engaged in negative reciprocity. This corroborates a favorable role of women in anticorruption. Businesspeople who strongly preferred a corrupt framing of the game and obtained a form with corrupt wording were more willing to punish non-delivering public servants. This operates against camouflaging a bribe as a gift, because gifts fail to signal negative reciprocity.
Keywords: D73; K42; C72; C91; 330; Corruption; ultimatum game; whistleblowing; gender; signaling; trust